CULTIVATIONOF PRAWNIN POLYCULTUREWITHSOME SPECIESOF INDIANAND CHINESE MAJOR CARPS (Biological Sciences - PJSIR, 2004)
The freshwater prawn Macrobrachium rosenbergii (de Man) was cultivated in polyculture with Indian and Chinese major carps for two successive years. The densities of prawn were 6000,8000 and 10,000 juveniles / ha with a constant fish density of 5,000 fish fingerlings / ha. The fish species were silver carp (35%), catla (15%), mrigal (20%) in the first year and in the second year silver carp, catla, rohu, mrigal, grass carp and black carp in the ratio of 30:15:34:5:15:1, respectively. Highest production of prawn and fish were 122 kg / ha and 4200 kg / ha / yr in the first year and 96 kg / ha and 3945 kg / ha / yr in the second year. The low production of prawn might be hampered by the low temperature. However, cultivation of prawn with Indian and Chinese major carps should be made in overwintering season and low prawn density should be maintained in polyculture system of M. rosenbergii with fish.